Illegal Online Gambling in Indonesia: Assessing State Securitization and Its Effectiveness - Azis, Aswin Ariyanto; Azhari , M. Irfan (Jurnal Hubungan Internasional, 2025)
After the COVID-19 pandemic, Southeast Asia has become a lucrative epicenter of illegal online gambling across borders. Illegal online gambling has emerged as a threat that harms the national interests of Southeast Asian nations. On the other hand, Indonesia is one of the Southeast Asian nations that has been struggling with the issue of illegal online gambling. Those harms encompass not only national economic loss, but also the socio-economic well-being of the citizens. This research analyzed the role of state actors in dealing with illegal online gambling compared to the offshore operations of illegal online gambling as transnational actors. The analysis of the securitization theory was taken under the framework of the Copenhagen School. Through the qualitative literature review method, this research discovered that the Indonesian government has played a pivotal role in combating illegal online gambling by securitizing it as an existential threat that harms its referent object. Hence, due to jurisdictional constraints, their effectiveness throughout their operation remained questionable. However, alternative solutions, such as strengthening international collaboration and communication, must always be assured.